A tunable hydrogel system for long‐term release of cell‐secreted cytokines and bioprinted in situ wound cell delivery. Issue 7 (28th June 2016) - Skardal, Aleksander; Murphy, Sean V.; Crowell, Kathryn; Mack, David; Atala, Anthony; Soker, Shay
Abstract: For many cellular therapies being evaluated in preclinical and clinical trials, the mechanisms behind their therapeutic effects appear to be the secretion of growth factors and cytokines, also known as paracrine activity. Often, delivered cells are transient, and half‐lives of the growth factors that they secrete are short, limiting their long‐term effectiveness. The goal of this study was to optimize a hydrogel system capable of in situ cell delivery that could sequester and release growth factors secreted from those cells after the cells were no longer present. Here, we demonstrate the use of a fast photocross‐linkable heparin‐conjugated hyaluronic acid (HA‐HP) hydrogel as a cell delivery vehicle for sustained growth factor release, which extends paracrine activity. The hydrogel could be modulated through cross‐linking geometries and heparinization to support sustained release proteins and heparin‐binding growth factors. To test the hydrogel in vivo, we used it to deliver amniotic fluid‐derived stem (AFS) cells, which are known to secrete cytokines and growth factors, in full thickness skin wounds in a nu/nu murine model. Despite transience of the AFS cells in vivo, the HA‐HP hydrogel with AFS cells improved wound closure and reepithelialization and increased vascularization and production of extracellular matrix in vivo . These results suggest that HA‐HP hydrogel has the potential to prolong the paracrine activity of cells, thereby increasing their therapeutic effectiveness in wound healing. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 105B: 1986–2000, 2017.